PEMIKIRAN PENDIDIKAN ISLAM MENURUT MUHAMMAD ‘ATHIYAH AL-ABRASYI - Mariani, Mariani (UIN Antasari Banjarmasin, 2022)
ABSTRACTMuhammad 'Athiyah al-Abrasyi is an Egyptian Muslim thinker. His thoughts related to Islamic education are relevant today, especially regarding the development of moral values by teachers and as students. Among the thoughts of Islamic education put forward by him are those regarding the goals of Islamic education, the urgency of education for women, the interaction between teachers and students, components of the Islamic education curriculum, and methods of moral education (morals). Actually, his thinking was heavily influenced by Muslim thinkers in the previous era, especially those related to philosophical aspects, such as Al-Gazali, Ibn Sina and Ibn Khaldun. In essence, reform in Islamic education is absolutely necessary in order to progress.KEYWORDS: Morals; Teacher; 'Athiyah al-Abrasyi; Student; Tarbiyah. ABSTRAKMuhammad ‘Athiyah al-Abrasyi adalah salah seorang tokoh pemikir muslim berkebangsaan Mesir. Pemikirannya terkait dengan pendidikan Islam relevan hingga kini, terutama terkait pembinaan nilai-nilai akhlak oleh guru dan sebagai murid. Di antara pemikiran pendidikan Islam yang dikemukakan olehnya adalah berkenaan dengan tujuan pendidikan Islam, urgensi pendidikan untuk para wanita, interaksi antara guru dengan murid, komponen kurikulum pendidikan Islam, dan metode pendidikan moral (akhlak). Sebenarnya, pemikirannya ini banyak dipengaruhi oleh para pemikir Muslim di era sebelumnya, terutama yang berkaitan dengan aspek filosofis, seperti Al-Gazali, Ibnu Sina dan Ibnu Khaldun. Hakikatnya, pembaharuan dalam pendidikan Islam mutlak untuk dilakukan dalam rangka menuju kemajuan.KATA KUNCI: Akhlak; Guru; 'Athiyah al-Abrasyi; Siswa; Pendidikan.